The BIOSURFACTANT AND ANTIMICROBIAL ACTIVITY OF LACTIC ACID BACTERIA ISOLATED FROM DIFFERENT SOURCES OF FERMENTED FOODS: BIOSURFACTANT AND ANTIMICROBIAL ACTIVITY OF LACTIC ACID BACTERIA - abdalsadiq, nagea kaream; Hassan, Zaiton (Asian Journal of Pharmaceutical Research and Development, 2018)
ABSTRACT Biosurfactants or surface-active compounds are biodegradable, non-toxic and ecofriendly compounds released by microorganisms. The purpose of this work was to evaluate the potential of lactic acid bacteria (LAB) present in fermented foods as biosurfactants producers and their antimicrobial activities against pathogenic bacteria. The results revealed that a total of twenty LAB were isolated from different sources of fermented foods and were screened for biosurfactant production and antimicrobial activity. Six isolates namely Fm1 isolated from fermented milk, Y1 isolated from Arabic yogurt, Gr isolated from fermented grape, So isolated from soil, Fm3 isolated from fermented milk and Y2 from Arabic yogurt produced biosurfactants with antimicrobial activities. Addition of cell free supernatant (CFS) from the six isolates reduced the surface tension of water from 72.22 mN/m to an average of 37.21 mN/m. The CFS of the six isolates showed emulsion index (EI24) of 90% for diesel and motor oil while 80% for crude oil. Additionally, the CFS of the six isolates showed strong inhibition activity against the target pathogens (P. florescence, P. aeroginosa ATCC2785, P. aeruginosa 14T28, E. coli and S. Typhimurium) with inhibition zone between 15 and 33.4 mm in diameter. Identification using 16s rDNA identified the isolates as L. acidophilus for Fm1, L. pentosus for Y1, L. fermentum for Gr, L. plantarum for So, L. lactis for Fm3 and L. casei for Y2. This study concluded that CFS of LAB isolated from fermented foods possess both biosurfactant and antimicrobial activities that could be further exploited for food and pharmaceutical applications.